Disparities in Depression Status Among Different Industries in Transition Economy: A Cross-Sectional Study of Mongolia. (May 2021) - Batbold, Ochirbat; Pu, Christy
Transition economies tend to rely on rapid growth of specific industries and hence often leads to disparities in health status among the working population. This study aims to determine the depression status in different industries and occupational groups in Mongolia, a country that is experiencing an economic transition. We conducted a cross-sectional survey between July and September 2018 in Ulaanbaatar, Mongolia. A total of 1784 employees from 22 private and public companies were enrolled in this study. The Patient Health Questionnaire–9 (PHQ-9) was used to determine the severity of depression. Prevalence of depression is evaluated using weighted analysis. The association between occupational groups (white, blue, and pink collars), industries, and PHQ-9 score was analyzed using linear regression. In multiple regression, the workers in the transportation, public administration, and education industries exhibited the highest depression scores ( P < .001). Traditional variables such as age, sex, and marital status remained significant predictors in our model. Industrial types should not be overlooked in identifying depression in the working population. This is especially true for a transition economy like Mongolia. Analysis by industries is essential to promote stress management in the future among vulnerable groups in specific industries.